SSUES OF DEVELOPMENT OF PRIVATE MEDICINE IN HEALTH CARE SERVICESS - Davron Kesimov , Bobomurodovich (THE INNOVATION ECONOMY, 2025)
This article reveals the regional aspects of private medicine in the healthcare sector and the principles of forming the mechanism and levers of the medical services market for the health of the population of the region. It is also argued that the settlement of market relations in healthcare, which is an integral part of the private medical services market in the healthcare sector, is due to the fact that the growth of utility bills, drug prices, maintenance of buildings, purchase of equipment and inventory, organization of patient nutrition, implementation of preventive measures and treatment of diseases, limits the capabilities of medical institutions.